IMMUNOHISTOCHEMICAL EXPRESSION OF MATRIX METALLOPROTEINASE-1 (MMP-1) IN DIFFERENT TYPES OF BREAST CARCINOMA AND ITS COMPARISON WITH ER/PER AND HER2/neu - Farwa Batool Shamsi; Ammara Anwar; Raees Abbas Lail; Mulazim Hussain Bukhari; Nadia Naseem; Abdul Hannan Nagi (Journal of Ayub Medical College Abbottabad, 2021)
Background: Breast cancer is a complex disease that comprises of various biological sub-types with different natural history. Matrix metalloproteinase-1(MMP-1) expression has been reported to inversely correlate with the survival. The current study was conducted to classify breast cancer into four subtypes based on IHC, to assess the immunohistochemical expression of MMP-1 in primary breast carcinoma, to compare its expression with ER/PR and HER2/neu. Methods: A descriptive study was conducted on 100 mastectomy specimens of breast carcinoma after being fixed in 10% formalin at Department of Histopathology, University of Health Sciences Lahore. Sections were taken on frosted slides for H&E and on lysine coated slides for immunohistochemistry (IHC). Haematoxylin and eosin (H&E) and IHC for oestrogen receptor/progesterone receptor (ER/PR), HER2/neu and Matrix metalloproteinase (MMP-1) were performed according to protocol. Results: The mean age was 48.44±11.79 Years (ranging 25 to 90 years). 97 cases were of Invasive ductal carcinoma (IDC) type, two showed the features of invasive lobular carcinoma and only one case was found to be of mucinous type, 19 cases were found to be in grade I, 74 in grade II and seven cases were in grade III. Breast cancer has been classified into four major groups based on IHC profile ER/PR and HER2/neu expression. The groups were: Triple positive, ER/PR+, HER2-, ER/PR-, HER2/neu+ and triple negative) cases. Among 100 cases of breast cancer, 9 were of triple positive type, (ER/PR +, HER2/neu+), 28 cases were of ER/PR +, HER2- type, 19 were ER/PR-, HER2/neu +ve and 44 cases were of triple negative type (ER/PR-, HER2/neu-ve). 13 cases were of score 1 MMP-1out of which 7 (25.0%) were ER/PR+, HER2-, 1 (5.3%) case was ER/PR-, HER2/neu +ve and 5 (11.4%) cases were triple negative. Among 30 cases of MMP-1 score 4, 5(55.6%) cases were of triple positive type, 3 (10.7%) cases were of ER/PR +, HER 2/neu-ve type, 12(63.2%) cases were of ER/PR-, HER 2/neu+ve type, and 10 (22.7%) cases were of triple negative type. A significant p-value of <0.05 was obtained. Conclusions: Among four IHC based subtypes, most frequent were triple negative breast cancers which showed high IHC score of MMP-I which is reported to be an important marker for metastatic potential in breast carcinoma.